Predictors Associated with Quality of Working Life Among Nurses in The Hospital Setting: a Systematic Scoping Review - Husin, Nurmila; Agustina, Hana Rizmadewi; Mediawati, Ati Surya (Universitas Malahayati, 2024)
ABSTRACT The level of Quality of Nursing Work Life (QNWL) in nurses is quite diverse and is also influenced by various factors. Identifying factors that influence QNWL is very important to increase job satisfaction which can increase nurse productivity. This study aims to identify the factors that affect the quality of work life in hospital nurse clinicians. This study used the scoping review method with the PRISMA ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) guidelines. The inclusion criteria used were articles with an RCT, cohort and cross-sectional design, in English and full-text. Some databases such as PubMed, Cinahl, and the search engine Google Scholar were used to search the study. We found 15 articles that met the criteria and came from 8 countries (Saudi Arabia, Portugal, Malaysia, Iran, Ethiopia, Indonesia, Jordan and Slovenia). The number of samples from the studies obtained varied quite widely from a minimum of 40 respondents to a maximum of 2391 respondents. The results of the analysis show that the QWL level of nurses working in hospitals is quite varied with the majority being in the low to moderate category (low score, 42-112 and moderate score, 113-182), three studies that obtained nurses' QWL results in the good range (high score, 183-252). Conclusion: An assessment of predictor factors of QNWL can help to make improvements to each factor in order to improve the nursing care services provided, and of course reduce the nurse turnover rate. Keywords: Hospital, Nurse, Predictors, Quality of Work Life